An Anatomic Approach for Intramedullary Screw Fixation of Fifth Metatarsal Fracture: A Clinical and Radiographic Study. Issue 4 (16th October 2019) - Niu, Shuo; Mirza, Faris; Schwartz, Andrew; Labib, Sameh
Category: Ankle, Sports, Trauma Introduction/Purpose: Intramedullary screw fixation is the most common surgical intervention for treating Jones fractures and diaphyseal stress fractures of the fifth metatarsal. Proper screw placement is paramount to surgical success. There have been studies describing more traditional antegrade and retrograde approaches, dependent upon fluoroscopy and guidewires. However, we propose a novel, more efficient surgical approach that utilizes anatomical landmarks and plantarflexion angle during screw fixation. The purpose of this study was to evaluate screw position and radiographic healing parameters, return to sport, and patient-reported outcome measures after utilization of our technique for screw fixation of the fifth metatarsal fracture. Methods: This is a retrospective review from 2007 to 2017 of clinical records and radiographs of 31 consecutive patients who had fifth metatarsal fracture open reduction internal fixation using anatomical landmarks and plantarflexion angle (Johnson, Labib and Fowler 2004). The classification of the fracture, surgery time, time to union, and post-operative complications were collected. Return to sport, Tegner score, the Foot and Angle Disability Index (FADI) Sports Module, and the Short Form 12 Physical and Mental Health Composite Scale (SF-PCS/MCS) were obtained through phone interview. Post-operative X-ray analysis, including screw position and bone healing percentage, were evaluated. Post-operative screw position was described as either center-center, oblique, or cortical breach on anteroposterior, lateral or oblique view. Fisher's exact test was used to determine the difference among frequencies of each screw position. P<0.05 was considered significant. Results: Patient and surgical information were shown in Table 1. Average post-operative follow-up was 98 (36-227) days. Screws were well center-center positioned at all three views on post-op X-ray in most cases (all p<0.001). No case showed the screw protruding into tarsometatarsal joint or cuboid impingement. Average phone interview follow-up was 5.4 (1.0-11.1) years. Tegner scores showed no difference (p=0.58) when compared between pre-injury (6.4) and current level (6.1). At the terminal follow-up, average FADI-sports was 87.2 (37.5-100), SF-PCS was 50.7 (27.3-55.6), and SF-MCS was 59.7 (52.9-67.2). In addition, 12 of 15 (80%) the college or professional athletes (1 lost to follow-up) returned to the same level sports after the surgery. Conclusion: This study quantified the benefit of a novel technique for intramedullary screw fixation of fifth metatarsal fracture that was reliable and reproducible. It facilitated accurate screw positioning, dependable union, and accompanying positive return to sport and patient-reported outcome measures.